HyperX: topology, routing, and packaging of efficient large-scale networks - Ahn, Jung Ho; Binkert, Nathan; Davis, Al; McLaren, Moray; Schreiber, Robert S. (Proceedings of the Conference on High Performance Computing Networking, Storage and Analysis, 2009)
In the push to achieve exascale performance, systems will grow to over 100,000 sockets, as growing cores-per-socket and improved single-core performance provide only part of the speedup needed. These systems will need affordable interconnect structures that scale to this level. To meet the need, we consider an extension of the hypercube and flattened butterfly topologies, the HyperX, and give an adaptive routing algorithm, DAL. HyperX takes advantage of high-radix switch components that integrated photonics will make available. Our main contributions include a formal descriptive framework, enabling a search method that finds optimal HyperX configurations; DAL; and a low cost packaging strategy for an exascale HyperX. Simulations show that HyperX can provide performance as good as a folded Clos, with fewer switches. We also describe a HyperX packaging scheme that reduces system cost. Our analysis of efficiency, performance, and packaging demonstrates that the HyperX is a strong competitor for exascale networks.